A Cinema of Boredom: Heidegger, Cinematic Time and Spectatorship. Issue 1 (February 2020) - Quaranta, Chiara
Abstract : Boredom, in cinema as well as in our everyday experience, is usually associated with a generalised loss of meaning or interest. Accordingly, boredom is often perceived as that which ought to be avoided. In Martin Heidegger's philosophical inquiry, however, boredom is posited as one of the fundamental existential dispositions that provide access to the possibility of philosophising. My contention is that boredom can be a tool for understanding spectatorship in cinema and, in contrast to the ordinary perception of boredom as something to escape, it can be a stimulus for reflecting on the images before us. To this end, I focus on Heidegger's tripartition of boredom – "becoming bored by something, " "being bored with something, " and "profound boredom" – and the ways in which these forms can be significant to cinema. I then consider boredom's potential for film spectatorship, differentiating between mainstream entertainment cinema as a means to evading boredom and less immersive forms of cinema which allow for boredom to remain present. On the one hand, "profound boredom" disrupts the potentially alienated relationship between spectators and spectacle-images by opening up a time which becomes long – something which Isidore Isou's On Venom and Eternity ( Traité de Bave et d'Éternité, 1951) and, less manifestly, Michelangelo Antonioni's L'Eclisse (1962) and Ingmar Bergman's Cries and Whispers ( Viskningar och rop, 1972) deliberately arouse. Thus, profound boredom can be a tool to criticise the spectacularised image in the cinema, promoting a pensive spectatorship. On the other hand, the escapism endorsed by mainstream narrative cinema can dialectically reveal the contemporary anxiety of horror vacui, therefore turning boredom into a means for investigating our relationship with time and the image. This article ultimately argues that boredom – that from which we daily try to shy away – has the potential to un-conceal the ways we understand and interact with moving images in the world we currently inhabit.